2019
DOI: 10.1155/2019/8715314
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Material in Secondary Orbital Reconstruction Surgery

Abstract: Purpose. To validate the potential of bioresorbable implantation in secondary revisional reconstruction after inadequate primary orbital fracture repair, with assessment of pre- and postoperative clinical characteristics and computed tomography image findings. Methods. A retrospective chart review was conducted on 16 consecutive patients treated for orbital fractures at Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, with inadequate prior surgeries between July 2010 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The present study is novel in presenting a large sample of patients who had undergone secondary orbital reconstruction with a PSI. The increased difficulties in secondary orbital reconstruction relating to scarring, distorted bony anatomy, soft tissue deformity, and the presence of pre-existing hardware has been described extensively in the literature 10,[35][36][37][38][39] . Several case studies describing PSI in secondary reconstruction have advocated their use specifically for secondary reconstruction 7,13,14,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study is novel in presenting a large sample of patients who had undergone secondary orbital reconstruction with a PSI. The increased difficulties in secondary orbital reconstruction relating to scarring, distorted bony anatomy, soft tissue deformity, and the presence of pre-existing hardware has been described extensively in the literature 10,[35][36][37][38][39] . Several case studies describing PSI in secondary reconstruction have advocated their use specifically for secondary reconstruction 7,13,14,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional repair materials for orbit are mainly composed of artificial materials that cannot be absorbed or degrade, therefore the long-term retaining of a foreign body results in an increased probability of complications such as infection and hemorrhage. 9 Along with the rapid development of tissue engineering, bioresorbable materials have become a hotspot and have been applied widely in clinic. 4 A 10-year retrospective study demonstrated the safety and effectiveness of bioresorbable materials in orbital fracture surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al could improve diplopia, exophthalmos, and ocular motility in 16 cases using Rapidsorb implants. 28 However, long-term results still have to follow and an ideal solution for secondary reconstruction has not yet been found. This innovative approach might be another step to provide best functional care and esthetic appearance for patients.…”
Section: Discussionmentioning
confidence: 99%